Uptake of health insurance and the productive safety net program in rural Ethiopia. (March 2017) - Shigute, Zemzem; Mebratie, Anagaw D.; Sparrow, Robert; Yilma, Zelalem; Alemu, Getnet; Bedi, Arjun S.
Abstract: Due to lack of well-developed insurance and credit markets, rural families in Ethiopia are exposed to a range of covariate and idiosyncratic risks. In 2005, to deal with the consequences of covariate risks, the government implemented the Productive Safety Net Program (PSNP), and in 2011, to mitigate the financial consequences of ill-health, the government introduced a pilot Community Based Health Insurance (CBHI) Scheme. This paper explores whether scheme uptake and retention is affected by access to the PSNP. Based on household panel data and qualitative information, the analysis shows that participating in the PSNP increases the probability of CBHI uptake by 24 percentage points and enhances scheme retention by 10 percentage points. A large proportion of this effect may be attributed to explicit and implicit pressure applied by government officials on PSNP beneficiaries. Whether this is a desirable approach is debatable. Nevertheless, the results suggest that membership in existing social protection programs may be leveraged to spread new schemes and potentially accelerate poverty reduction efforts. Highlights: Bundling social protection programs enhances uptake of health insurance. Membership in an existing program boosts insurance uptake by 24 percentage points. Membership in an existing program enhances retention by 10 percentage points. Higher uptake is driven by explicit and implicit pressure exerted by officials.